Ultrasound technique for the assessment of urethral descent assessment technique (UDAT) in healthy volunteers. (2nd April 2020) - Asfour, Victoria; Gibbs, Kayleigh; Franklin, Larissa; Digesu, Giuseppe Alessandro; Fernando, Ruwan; Regan, Lesley; Khullar, Vik
Abstract: Bladder neck descent (BND) has been implicated in the pathophysiology of stress incontinence and prolapse. The aim of this study was to evaluate a novel 2D technique for the evaluation of BND, the Urethral Descent Assessment Technique (UDAT). UDAT involves measuring BND during dynamic manoeuvres in live 2D ultrasound, by using the geometrical properties of parallel lines. The internal urethral meatus and distal end of the urethra are used as reference points. Y1 is the urethral height at rest (also the urethral length when the urethra is straight). Y2 is the urethral height on Valsalva. Y1 and Y2 are parallel lines. Y1 –Y2  = BND. A horizontal line (X) connecting Y1 and Y2 is the forward movement of the bladder neck. Y1 mean 30.4 mm (95% CI ± 1.36 mm). Y2 mean 24.2 mm (95% CI ± 2.58 mm). X mean 12.1 mm (95% CI ± 1.66 mm). BND mean 6.2 mm (95% CI ± 1.47 mm). Bland–Altman plots and linear regression showed that UDAT is repeatable and reliable. Impact statement: What is already known on this subject? Bladder neck descent (BND) has been associated with stress incontinence and prolapse nearly a century. In 1975, Green introduced a classification based on X-ray cysto-urethrograms. Between 1989 and 1995, a 2D technique was described that had several limitations. What do the results of this study add? This study validates a novel technique for the assessment of bladder neck descent using 2D ultrasound and provides a reference range of BND for normal nulliparous women. What are the implications of these findings for clinical practice and/or further research? This is a simple and quick technique that could be adopted in research and clinical practice in the future to assess stress incontinence and anterior compartment prolapse.